Masseter muscle rigidity and the role of DNA analysis to confirm malignant hyperthermia susceptibility. Issue 1 (January 2019) - Hudig, Kate; Pollock, Neil; Bulger, Terasa; Machon, Roslyn G; Woodhead, Andrew; Schiemann, Anja H; Stowell, Kathryn M
Malignant hyperthermia (MH) is an uncommon, autosomal dominant disorder of skeletal muscle, triggered by inhalational anaesthetics or depolarizing muscle relaxants. Masseter muscle rigidity (MMR) can be regarded as potentially a preceding sign for an MH reaction. Susceptibility to MH can be determined by the in vitro contracture test (IVCT) or DNA analysis where a familial variant is known. Our aims were to review patients with MMR, where IVCT and DNA analysis had been undertaken, to determine if DNA analysis could be used as an initial screening tool for MH susceptibility, and, by reviewing standard monitored variables (SMVs), to determine if any clinical characteristics could be used to differentiate between MMR patients who are MH susceptible (MHS) and those who are not. Patients with MMR were identified from the Palmerston North Hospital MH Reactions Database. IVCT and DNA analysis results were documented. DNA testing was performed retrospectively in the majority of patients as many patients had presented before DNA analysis was available. Forty-one patients were analysed. Fourteen were DNA positive/IVCT positive and six DNA positive only (48% in total), seven were IVCT positive/DNA negative and 14 were IVCT normal. Increased creatine kinase (>18, 000 units/L) was consistent with MH susceptibility. Severity of MMR was not linked to MH susceptibility. This study confirmed that DNA analysis can be used as a first-line test for MH susceptibility in patients presenting with MMR (consistent with European MH Group recommendations). Creatine kinase was the only SMV that was significantly different between MHS and MH normal individuals.